Hubungan Pencapaian Kompetensi Pendidikan Anak Usia Dini (PAUD) Dengan Perkembangan Motorik Halus Pada Anak Usia Pra Sekolah (4 Tahun) di PAUD TK Al Hidayah Purwokerto Srengat Blitar - Aulia Rizqi Nadia R; Neny Triana (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2018)
Competence is a capability that can be achieved by the child's age. it is also supported by the motivation of children so as to encourage the development of children in the sense that children are not forced to do something, but also the psychological readiness of children to achieve the level of child development in early childhood TK Al-Hidayah Purwokerto Srengat Blitar. Smooth motor development of the child will be more optimal if the child gets stimulation on the fine motor physical ability, where the child in the ability to move the smooth muscles in the drawing and writing activities. The purpose of this research is to know the relation of Achievement of Early Childhood Education Competence (PAUD) with Motorcycle Development of Pre School Pre School 4 years in PAUD Kindergarten Al-Hidayah Purwokerto Srengat Blitar. The design of this study was cross-sectional. Population were 9 respondents, sample were 9 respondents, with total sampling technique. The data were collected using documentation of second semester report value and observation of fine motor development with denver II. Results of research with cross tabulation between achievement of competence with fine motor development. Data were analyzed by spearman rho test, significance level α < 0,05. The results showed that p = 0.02, the correlation coefficient = 0.880 indicates a correlation between the achievement of competence with fine motor fertilizer preschool children. The result of the research was obtained from 9 respondents: 6 respondents (66,7%) achievement of good competence, 1 respondent (11,1%) achievement of competence enough, 2 respondents (22,2%) achievement of competence need to be trained. Most of the respondents have good competence, this is influenced by age and environment. It is expected that the respondents increase the motivation to learn, to improve the smooth motor development. It is also expected that the parents of the respondents to increase knowledge about the fine motor development of children that must be achieved based on age.